2018
DOI: 10.1088/2399-6528/aae0dc
|View full text |Cite|
|
Sign up to set email alerts
|

Fermi surface pockets in electron-doped iron superconductor by Lifshitz transition

Abstract: The wavefunction renormalization Z(k′, ω) that appears on the right-hand side of the Eliashberg Equations listed in equation (58) of section 4.2 and in equations (D.1), (D.2) and (D.3) of appendix D must be replaced by Z(k′, ω′), where ω′ = E(k′). It must also be added that the subsequent Eliashberg equations (59a) and (59b) in section 4.3 are achieved under the approximation that the above corrected wavefunction renormalization on the righthand side of equation (58) is replaced by its value at the Fermi level… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(49 citation statements)
references
References 47 publications
(180 reference statements)
0
49
0
Order By: Relevance
“…Thus, it demonstrated that a synergistic effect between possible spin fluctuations and enhanced EPI results in such high T c in FeSe/STO. It is worth noting that theorists could qualitatively describe the Fermi surface, hidden magnetic order, replica bands, and the superconductivity isotropic Cooper pairs in heavily electron-doped FeSe by an extended Hubbard model [99,100]. Such explanations could deepen the understanding of the superconducting mechanism and may help us explore more high T c superconductors.…”
Section: Superconductivity Of Fese Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it demonstrated that a synergistic effect between possible spin fluctuations and enhanced EPI results in such high T c in FeSe/STO. It is worth noting that theorists could qualitatively describe the Fermi surface, hidden magnetic order, replica bands, and the superconductivity isotropic Cooper pairs in heavily electron-doped FeSe by an extended Hubbard model [99,100]. Such explanations could deepen the understanding of the superconducting mechanism and may help us explore more high T c superconductors.…”
Section: Superconductivity Of Fese Filmmentioning
confidence: 99%
“…It also implies that a higher T c will appear in the FeSe film if the lattice constants are expanded and higher electronic doping is introduced. Rebec et al compared the T c and the scale of superconducting gap in 60 unit-cell FeSe/STO (001), SUC FeSe/STO (001), and 3 UC FeSe/STO (001) coated by potassium atoms and SUC FeSe/TiO 2 (100). By analyzing the ARPES results, they found that electron doping plays an important role in inducing high T c [93].…”
Section: Superconductivity Of Fese Filmmentioning
confidence: 99%
“…Recent theoretical work suggests that the "rings" and "diamonds" of spin excitations observed in electron-doped FeSe at the checkerboard wavevector are due to proximity to a hidden spin-density wave (hSDW) state 17,18 . Here, the sign of the ordered magnetic moment alternates between the principal d+ = (d xz + id yz )/ √ 2 and d− = (d xz − id yz )/ √ 2 orbitals of the iron atom, as well as between the "white" and the "black" sites on the checkerboard of iron atoms 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown by the author and a co-worker that fluctuation-exchange with Goldstone modes associated with such hidden magnetic order results in a Lifshitz transition to electron/hole Fermi surface pockets at the corner of the folded Brillouin zone 18 . (See Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation